People Who Make Our History: Murtala Ramat Muhammed (1933 - 1976) - Winclair, J.E Asunwontan (Evans Brothers (Nigeria Publishers) Ltd, 2012)
Murtala Ramat Muhammed is one of the collections in the People Who Make Our History series. The assortment is a range of short story books about the heroic deeds of notable people worthy of emulation both in the past and present...
Keywords: Juvenile Non-Fiction / Biography-Murtala Ramat Muhammed